THE ANALYSIS OF INTERLINGUAL AND INTRALINGUAL ERRORS IN THE WRITINGS OF THAI UNIVERSITY STUDENTS - Tipprachaban, Benjawan (วารสาร มจร พุทธปัญญาปริทรรศน์, 2024)
The primary objective of this study was to investigate the occurrence of interlingual and intralingual errors in the written compositions of Thai university students. The study also identified the types of errors Thai students struggled with most. The study included 41 Suratthani Rajabhat University third-year English majors. The research instrument utilized in this study was a form of unstructured writing known as free writing. Every individual was required to fulfill the task entitled "My Dream." The analysis and categorization of students' writing was conducted through the utilization of James' error taxonomy. The identification of error sources was conducted using a diagnosis-based analysis. The findings revealed that within the Common European Framework of Reference for Languages (CEFR), intralingual errors, particularly those related to grammar, presented the most significant difficulty across all proficiency levels. Of all 6,104 words written by all levels, a total of 1,521 errors were detected, with the majority (1,440 errors) falling under the classification of intralingual errors, while a considerably smaller proportion (81 errors) were identified as interlingual errors. Notably, students at the A2 level demonstrated the highest occurrence of grammar errors, constituting 18.99% of the total words written. The subsequent distribution consisted of B2 level students comprising 17.42%, C1 level students comprising 14.08%, A1 level students comprising 13.09%, and B1 level students comprising 12.05%. The results also showed that CEFR levels did not statistically affect English writing proficiency. This suggested that higher CEFR levels did not necessarily improve English writing.